Increased Interest in Learning Through Smart Apps Creator - Sagala, Ronal; Simanungkalit, Malani (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
Reading is huge because reading is a source of information, but most of the learners open social media more often, play games with laptops or gadgets, compared to reading. Using teaching materials in supporting the teaching learning process can help students more easily understand the learning material, because it is undeniable that the development of teaching materials is very important in learning, so the more interesting the teaching materials used, the more interested students will be in the teaching materials. The purpose of this research is to determine the development of application-based teaching materials and to determine student responses to application-based teaching materials in the Church Administration and Management course in the Christian Leadership Study Program. The results of the study are calculatedbased on the validity calculation formula, then an average score of 3.1875 is obtained with decent criteria. Through this research, it is hoped that the application-based Church Administration and Management teaching program (Smart Apps Creator) is used by students as a practical learning medium and can be used anytime and anywhere